Investigation of acidity on corrosion behavior and surface properties of SS304 in simulated PEMFC cathode environments. (29th June 2022) - Xuan, Junji; Liu, Yueren; Xu, Likun; Bai, Shuangfeng; Xin, Yonglei; Wang, Li; Zhang, Guodong; Su, Yan; Xue, Lili; Li, Li
Abstract: This study presents the influence of acidity on the corrosion performance and surface properties of AISI 304 stainless steel (SS304) in the simulated cathode condition of proton exchange membrane fuel cells (PEMFC) with various concentrations of H2 SO4 . The electrochemical tests indicate that the corrosion resistance of SS304 samples decreases gradually with the solution acidity ascending, but the stable current densities (0.043–0.547 μA cm −2 ) in the simulated solutions after polarization (0.6 V, 5 h) are all lower than that of the relevant DOE 2025 target ( i corr < 1 μA cm −2 ). Obvious pitting corrosion occur in the solutions with H2 SO4 concentration higher than 10 −3  M. The surface wettability and interfacial contact resistance (ICR) of the potentiostatically polarized SS304 show an upward trend with the solution acidity increasing, and whether the SS304 samples are polarized or not, their ICR (0.274–1.232 Ω cm 2 ) is far higher than the latest DOE 2025 technical target (<0.01 Ω cm 2 ). The results reveal that surface modification is indispensable for SS304 as bipolar plates, and more attention should be paid to possessing high and stable pitting resistance, hydrophobicity, and interfacial conductivity in an acid environment. Highlights: SS304 spontaneously passivates in solutions with H2 SO4 concentration below 10 −1  M. The oxide films formed after potentiostatic polarization are bilayer semiconductor. Pitting corrosion occurs in solutions with H2 SO4 concentration higher than 10 −3  M. The corrosion and wettability of SS304 increase with solution acidity. The ICR of SS304 first increases and then decreases with solution acidity.